Simulation: Is it the Future of Training in Critical Care Medicine? - Kulkarni, Atul P (Indian J Crit Care Med, 2019)
How to cite this article: Kulkarni AP. Simulation: Is it the Future of Training in Critical Care Medicine? IJCCM 2019;23(11):495–496.